Evaluation of cerebrovascular reactivity using transcranial Doppler in patients with influenza - Ana Orsolic Beslic; Kresimir Caljkusic; Antonela Matana; Katarina Tomelic Ercegovic; Mirela Pavicic Ivelja (PLoS ONE, 2026)
Influenza is primarily a respiratory disease but can cause a broad spectrum of complications, including those affecting the cerebrovascular system. The aim of this study was to evaluate cerebrovascular reactivity in patients during and after influenza infection. A total of 92 participants, mean age 43 years, were enrolled; 46 patients with confirmed influenza infection and 46 healthy controls. Cerebrovascular reactivity was assessed using transcranial Doppler in combination with the breath-holding test and quantified by the breath-holding index (BHI). The influenza group demonstrated significantly lower cerebral blood flow velocities in the middle cerebral artery both at rest (PSVrest, MVrest, p < 0.001) and after the breath-holding test (PSVmax, MVmax, p < 0.001) compared to healthy controls. The BHI was also significantly reduced in the influenza group ( p < 0.001), indicating impaired cerebrovascular reactivity. Among participants reassessed three months post-recovery, blood flow velocities after the breath-holding test were significantly higher than during the acute phase (PSVmax, MVmax, p < 0.001), and BHI also improved ( p < 0.001), suggesting restoration of cerebrovascular function. These findings suggest that influenza may transiently impair cerebrovascular reactivity, providing new insights into potential mechanisms influencing cerebrovascular function and hemodynamics.